On faith : lessons from an American believer - Scalia, Antonin (Crown Forum, 2019)
On Faith is an inspiring collection of the late Supreme Court justice Antonin Scalia's reflections on his own faith, on the challenges that religious believers face in modern America, and on the religious freedoms protected by the Constitution. Featuring a personal introduction by Justice Scalia's son Father Paul Scalia, this volume will enrich every reader's understanding of the legendary justice.